Intentional infliction of mental harm - Chang, Po-Yuan (The University of Edinburgh, 2019)
The aim of this thesis is to deal with the liability elements of the delict or tort of intentional infliction of mental harm, or, more precisely, to explore questions arising from the three essential elements of the Wilkinson v Downton tort reformulated in Rhodes v OPO. To tackle these issues, this thesis is divided into four main chapters (chapters 2 to 5), followed by chapter 6 which provides the conclusion. The conduct element of the Wilkinson/Rhodes tort, or the tort of intentional infliction of mental harm, will be investigated in chapter 2, which will be further divided into three parts. Part A provides the general introduction of conduct element, where the construction of conduct patterns of this tort through a combination of different types of conduct and various aggravating factors will be proposed. In Part B, the three archetypal conduct patterns of this tort will be dissected and then compared to other five recognised torts/delicts, to draw the boundaries and see the applicability of this tort beyond these recognised torts/delicts. In Part C, the role played by the requirement of ‘no justification or excuse’ in respect of the conduct element will be probed, and the potential justificatory grounds for conduct of this tort will then be explored. The mental element of the Wilkinson/Rhodes tort will be investigated in chapter 3. This thesis will argue that, in addition to ‘intention based upon purpose (ends or means)’, the mental element of this tort should also include ‘intention based upon knowledge (foresight with substantial certainty)’, whilst ‘recklessness’ should be excluded. Inferred or constructive foresight/intention should be accepted for these purposes, along with actual or subjective foresight/intention. Where the object of intention can be perceived as ‘(severe) mental or emotional distress’, the notion of ‘foresight with substantial certainty’ may arguably be regarded as the most suitable interpretation of the equivocal term ‘calculated’. The consequence element of the Wilkinson/Rhodes tort will be investigated in chapter 4. After examining the traditional distinction between recognised psychiatric illness and mere emotional distress, the boundary of mental harm will be delineated as deviation from normal or trivial emotions. Arguably, this concept of mental harm can be differentiated from recognised psychiatric illness as well as from mere emotional distress. Whether or not recognised psychiatric illness, as the traditional threshold of compensable damage of this tort, can to some extent be lowered will then be explored. If it is warranted that this traditional threshold can be lowered to ‘mental harm’ or ‘severe/significant emotional distress’, the relevant criteria for finding ‘mental harm’ will be analysed with examples. Issues regarding secondary victims in the realm of intentional infliction of mental harm will be investigated in chapter 5. First of all, it will be argued that secondary victims, whose mental harm is inflicted intentionally rather than negligently, should be entitled to a claim based upon this tort. Thereafter the prerequisites of this sort of claim will be explored. It will be argued that the prerequisites suggested, particularly in regard to the mental element, can adequately ring-fence liability for secondary victims in this intentional field. The limiting factors as regards proximity, as employed in negligence cases, remain important considerations in respect of this tort, although they need not be adopted as categorical limitations. Based upon these analyses and arguments, in chapter 6 a reconstructed framework of the Wilkinson/Rhodes tort will be proposed, which can arguably furnish answers to the long-debated problems in regard to this tort.
Keywords: liability; intentional infliction of mental harm; emotional distress; Wilkinson v Downton; Rhodes v OPO; foresight with substantial certainty